Catechol-alkali metal ion autocatalytic hydrogel electrolyte with high adhesion strength and anti-freezing performance and application of catechol-alkali metal ion autocatalytic hydrogel electrolyte
By using dopamine modified sodium alginate and lithium chloride in hydrogel electrolytes, and adding low co -melting solvents to solve the problem of freezing and insufficient adhesion at low temperatures at low temperatures, it has achieved efficient and efficient and efficient, and achieves efficient and efficient, Quickly prepare a hydrogel electrolyte with excellent frost resistance and conductivity, which is suitable for high -performance energy storage devices.
Patent Information
- Application Number
- CN202411484891.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
Hydrogel electrolytes are prone to freeze at low temperatures, limiting ion migration; their weak adhesion leads to insufficient interface contact during manufacturing and operation of energy storage devices, affecting overall performance; and the preparation process is cumbersome and requires additional energy.
By using dopamine-modified sodium alginate (SD) and lithium chloride (LiCl) to promote the balance of redox reactions, and polymerizing acrylamide (AM) in their presence, we prepared a polymer with high adhesive strength and antifreeze properties. of hydrogel electrolytes. A deep eutectic solvent (DES) is added to the electrolyte to destroy the hydrogen bonds between water molecules and enhance the antifreeze performance.
Achieved a fast aggregation of hydrogel electrolytes with excellent frost resistance and electrical electrostatic without additional energy. The adhesion reaches 2.16MPa, and the conductivity reaches 1.58MS CM-1 when the conductivity is at -40 ° C. Keep 89.7%of the capacitance after 2000 bending/release cycles.
Smart Images

Figure CN119361336A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to a catechol-alkali metal ion self-catalytic hydrogel electrolyte with high adhesion strength and antifreeze performance and application thereof. Background Art
[0002] As global energy consumption continues to increase, the demand for efficient electrochemical energy storage is also increasing. Hydrogel electrolytes are considered to be ideal candidates for energy storage due to their mechanical flexibility, good conductivity and safety. Nevertheless, hydrogel electrolytes still face three key challenges. First, the water solvent in hydrogel electrolytes easily freezes at sub-zero temperatures, which in turn limits ion migration at low temperatures. Second, the weak adhesion of hydrogel electrolytes leads to insufficient interfacial contact between hydrogel electrolytes and substrates during the manufacturing and operation of energy storage devices, thus affecting the overall performance of the device. Third, in order to meet these demanding requirements, the preparation of hydrogel electrolytes usually involves cumbersome and time-consuming manufacturing steps, and requires additional introduction of external energy such as ultraviolet light or heating to initiate free radical polymerization. Therefore, it is a huge challenge to obtain hydrogels with antifreeze and strong adhesion through rapid polymerization without the need for additional energy.
[0003] In general, conventional hydrogel electrolytes freeze below zero degrees, resulting in loss of adhesion and conductivity. The main reason for water freezing is that disordered water molecules rearrange to form an ordered ice structure at subzero temperatures, a process driven by the formation of additional hydrogen bonds. Adding high concentrations of salt to aqueous solutions is an effective way to prevent water from freezing because it can destroy the hydrogen bonds between water molecules, thereby inhibiting the formation of ice crystals. However, high concentrations of salt are corrosive to energy storage devices. In recent years, deep eutectic solvents (DES) have attracted much attention due to their low freezing point, easy synthesis, non-toxicity, and non-corrosiveness. Adding DES to hydrogel electrolytes is an effective candidate for providing antifreeze properties.
[0004] Strong adhesion usually requires hydrogels to meet two principles at the same time. One is to maximize the interaction between the hydrogel and the substrate, and the other is to enhance the cohesion of the hydrogel. The former requires special surface treatment, such as introducing various functional groups on the hydrogel or substrate to form strong chemical and physical bonds at the interface. The latter requires sufficient physical or chemical cross-linking to maintain the stability and integrity of the hydrogel network through energy dissipation when subjected to external forces. At present, an effective method to construct highly adhesive hydrogels is to add catechol-containing compounds such as polydopamine, tannic acid and tea polyphenols to the hydrogel matrix. Due to the characteristics of the catechol structure, it can achieve strong adhesion to various substrates by forming a variety of interactions, including hydrogen bonds, cation-π interactions and metal coordination bonds. However, most hydrogels only enhance adhesion by adjusting interfacial interactions, and rarely enhance adhesion by increasing cohesive energy. Summary of the invention
[0005] In order to make up for the deficiencies of the prior art, the present invention provides a catechol-alkali metal ion self-catalytic hydrogel electrolyte with high adhesion strength and antifreeze performance and application thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a catechol-alkali metal ion autocatalytic hydrogel electrolyte having high adhesion strength and antifreeze performance, wherein the hydrogel electrolyte is prepared by the following method:
[0008] Step 1: Synthesis of dopamine-modified sodium alginate SD
[0009] SD was synthesized using standard carbodiimide coupling chemistry, EDC / NHS;
[0010] Sodium alginate was dissolved in distilled water, stirred, and dissolved in a nitrogen atmosphere to prepare a 2.5wt% homogeneous sodium alginate solution; EDC and NHS were slowly added, reacted at room temperature for 3 hours, dopamine hydrochloride was added, the pH was adjusted to 7.8 with sodium hydroxide solution, and reacted at room temperature for 24 hours; finally, under the protection of nitrogen, unreacted reactants were removed by dialysis, and the product was freeze-dried;
[0011] Step 2: polyAM-SD x -LiCl y -DES z Preparation of electrolyte:
[0012] To prepare the deep eutectic solvent DES, choline chloride ChCl and ethylene glycol EG were mixed and stirred at 80°C until a transparent liquid was obtained to obtain DES; in the presence of SD and lithium chloride, polyAM-SDx-LiCly-DESz hydrogel electrolyte was obtained by polymerization of acrylamide AM; x is the mass fraction of SD, y is the molar concentration of LiCl, and z is the volume percentage of DES.
[0013] Furthermore, at -40°C, 1.58 mS cm -1 , and strong adhesion 2.16MPa.
[0014] Furthermore, in the step 1, 3.451 g of EDC and 2.072 g of NHS were added, and 0.6 g of dopamine hydrochloride was added to the solution.
[0015] Furthermore, in the step 2, the molar ratio n(ChCl):n(EG)=1:2.
[0016] Furthermore, step 2 is as follows:
[0017] First, lithium chloride was added to a mixture of DES and water with a DES volume fraction of 0, 20, 40, 60, and 80% to prepare a lithium chloride concentration of 0-7M, and then AM was added; then SD with a mass ratio of 0.3wt%, 0.6wt%, 1.2wt%, 1.2wt%, 1.8wt%, and 2.4wt% was added to the lithium chloride solution, and then MBA was added and stirred in an ice bath for 1 hour. Initiator APS was added, equivalent to 1% of the monomer mass, and then stirred in an ice bath; the precursor solution was injected into the mold and sealed at room temperature for polymerization.
[0018] In a second aspect, the present invention provides a supercapacitor, the supercapacitor comprising polyAM-SD x -LiCl y -DES z Hydrogel electrolyte.
[0019] In a third aspect, the present invention provides a method for assembling a supercapacitor, comprising the following steps:
[0020] First, activated carbon AC, conductive carbon black, and polyvinylidene fluoride PVDF were ground and N-methylpyrrolidone NMP was added to form a uniform dispersion; the dispersion was then uniformly applied on carbon cloth and placed in a vacuum oven at 180 °C for 24 h to obtain an AC electrode; the mass of active material on each electrode was recorded; two AC electrodes with the same mass of loaded active material were covered on polyAM-DL 0.1 -LiCl 3The hydrogel electrolyte is placed on both sides to produce a “sandwich structure” of solid SC.
[0021] Compared with the prior art, the benefits of the present invention are as follows: The present invention reports a simple and rapid preparation of a hydrogel electrolyte with high adhesion and antifreeze properties. Sodium alginate (SD) and lithium chloride (LiCl) modified by dopamine promote the balance of redox reactions and complete the polymerization of acrylamide within 80 seconds. The antifreeze property of the polyacrylamide hydrogel electrolyte is attributed to the formation of hydrogen bonds between the deep eutectic solvent (DES) and water molecules. The catechol groups in SD enable the hydrogel electrolyte to adhere to different substrates even in liquid nitrogen. By adjusting the content of DES, SD and LiCl, the preferred hydrogel electrolyte has excellent antifreeze and conductivity (1.58mS cm at -40°C). -1 ) and strong adhesion (2.16MPa). The supercapacitor assembled with hydrogel electrolyte can withstand dynamic deformation, and due to the good adhesion of the electrolyte / electrode interface, the capacitance retention rate is 89.7% after 2000 bending / release cycles. This invention provides a powerful strategy for the rapid preparation of highly adhesive and antifreeze hydrogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described below in conjunction with the accompanying drawings.
[0023] Figure 1 A schematic diagram of the rapid preparation of a highly adhesive and antifreeze hydrogel according to the present invention;
[0024] Figure 2 . The influencing factors and mechanism of rapid gelation of the present invention: a) Images of solution-gel transition and self-exothermic process of poly AM-SD in the absence and presence of LiCl at room temperature; Effects of different LiCl contents (b), SD contents (c), DES contents (d) and temperatures (e) on gel time; High-resolution XPS spectra of the C1s region of SD solution without LiCl (f) and SD solution with LiCl (g) to illustrate the oxidation degree of SD; h) UV-VIS spectra of SD solutions with different LiCl concentrations; i) ESR spectra of SO4-· and OH· captured by 5,5-dimethyl-1-pyrroline-N-oxide (DMPO); j) Schematic diagram of rapid gelation mechanism. Error bars represent the standard deviation of n≥3 samples;
[0025] Figure 3 Adhesion performance of hydrogels a) Schematic diagram of adhesion failure; b) polyAM-SD with different SD contents x -LiCl5-DES 20 Characterization curves of adhesion and displacement of hydrogel on wood substrate; c) Photograph showing polyAM-SD1.8 -LiCl5-DES 20 The hydrogel has excellent adhesion to wood; d) polyAM-SD 1.8 -LiCl5-DES 20 Adhesion mechanism of hydrogel; e) polyAM-SD 1.8 -LiCl5-DES 20 Photo of cohesive failure of hydrogel in lap shear test; f) polyAM-SD 1.8 -LiCl5-DES 20 The adhesion strength of the hydrogel changes with the water content; g) polyAM-SD with different water contents 1.8 -LiCl5-DES 20 Tensile stress-strain curve of hydrogel; h) Relationship between adhesion shear force and hydrogel thickness; i) polyAM-SD 1.8 -LiCl5-DES 20 Adhesion strength of hydrogel on different substrates; j) Photo of hydrogel (10 mm × 25 mm) adhered to wood with a load of 55 kg. Error bars represent the standard deviation of n ≥ 3 samples;
[0026] Figure 4 The antifreeze performance and ionic conductivity of the hydrogel of the present invention. a) polyAM-SD 1.8 -LiCl y -DES z Stretching photos of hydrogel electrolyte at room temperature and -60°C; b) polyAM-SD with different DES concentrations 1.8 -LiCl5-DES z Raman spectra and (c) DSC curves of hydrogel electrolytes; d) polyAM-SD 1.8 -LiCl y -DES 20 Temperature dependence of ionic conductivity of hydrogel electrolyte; e) Schematic diagram of adhesion and conductivity test at low temperature; f) Photo of macroscopic adhesion and conductivity test in liquid nitrogen (steel plate, 10mm*25mm);
[0027] Figure 5 Electrochemical performance of SCs of the present invention a) CV curve, b) GCD curve, c) EIS curve of SC at different temperatures; d) defects of traditional hydrogel electrolyte SC devices during continuous mechanical deformation; e) capacitance retention rate of SC after different bending angles, embedded as current density of 0.125A g -1f) GCD curves of SC after 180° bending for different time periods; g) Capacitance retention of SC device during 2000 bending / releasing cycles, the inset represents a complete cycle; h) CV curves of one SC device and two devices in series; i) Photo of five SCs lighting up an LED lamp after 2000 180° bending cycles at -40°C;
[0028] Figure 6 The binding efficiency of SA Sodium alginate and DA dopamine hydrochloride of the present invention is determined. (a) Chemical structures of SA, DA and SD. (b) UV-visible spectra of DA at different concentrations (0.25-1.25 mM). (c) Calibration curve of DA concentration. (d) -1 ;
[0029] Figure 7 is the chemical structure of ChCl, EG and DES of the present invention;
[0030] Figure 8 It is an instantaneous heat map of the self-exothermic process of the polyAM-SD1.8-LiCl5-DES20 hydrogel of the present invention during the gelation process at room temperature;
[0031] Fig. 9 The photos of polyAM-SD1.8-LiCl5-DES20 hydrogel of the present invention adhered to metal, plastic, glass, wood, polytetrafluoroethylene and rubber;
[0032] Fig.10 It is a schematic diagram of the quantitative analysis of hydrogel adhesion by lap shear strength test of the present invention.
[0033] Fig.11 The photographs of the present invention's separated samples provide an intuitive view of hydrogel adhesion and rupture. As shown in the figure, the separation mainly occurs in the bulk of the hydrogel.
[0034] Fig.12 is the modulus of the polyAM-SD1.8-LiCl5-DES20 hydrogel with different water contents of the present invention.
[0035] Fig.13 Photograph of the assembly of SC with polyAM-SD1.8-LiCl5-DES20 electrolyte using activated carbon electrode in the present invention.
[0036] Fig.14 CV curves of the present invention at (a) different voltage windows and (b) different scanning speeds at 25°C.
[0037] Fig.15 This is the GCD curve of the present invention at different current densities at 25C.
[0038] Fig.16 This is a schematic diagram of the SC bending angle of the present invention. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the embodiments.
[0040] Example 1
[0041] 1.1 Experimental section
[0042] 1.1.1 Raw materials and reagents
[0043] Table 3.1 Main raw materials and reagents
[0044]
[0045] 1.1.2 Experimental instruments and equipment
[0046] Table 3.2 Main experimental instruments and equipment
[0047]
[0048]
[0049] 1.1.3 Experimental sample preparation
[0050] 1.1.3.1 Synthesis of SD
[0051] SD was synthesized using standard carbodiimide coupling chemistry (EDC / NHS). Dissolve 0.75 g of sodium alginate in 30 ml of distilled water, stir, and dissolve under a nitrogen atmosphere to prepare a 2.5 wt% uniform sodium alginate solution. Slowly add EDC (3.451 g) and NHS (2.072 g) in sequence, react at room temperature for 3 hours, then add 0.6 g of dopamine hydrochloride to the solution, adjust the pH to 7.8 with NaOH solution, and react at room temperature for 24 hours. Finally, under nitrogen protection, dialyze with distilled water to remove unreacted reactants, and the product is freeze-dried. The connection efficiency of SD was determined by the UV calibration curve (see Figure 6 ).
[0052] 1.1.3.2polyAM-SD x -LiCl y -DES z Preparation of electrolyte:
[0053] To prepare a deep eutectic solvent (DES), ChCl (2.327 g) and EG (2.068 g) were mixed. In this embodiment, the molar ratio n (ChCl): n (EG) = 1:2 was sufficient. Stir at 80 ° C until a transparent liquid was obtained. In the presence of SD (sodium alginate modified by dopamine) and lithium chloride, polyAM-SDx-LiCly-DESz hydrogel electrolyte was obtained by AM (Acrylamide) polymerization. First, lithium chloride was added to a mixture of DES and water (DES: 0, 20, 40, 60, 80%) to prepare a concentration of 0-7M, and then 2g AM was added. Then, SD with different mass ratios (0.3wt%, 0.6wt%, 1.2wt%, 1.2wt%, 1.8wt%, 2.4wt%) was added to 5.0ml lithium chloride solution, followed by 2mg MBA (N,N-methylenebisacrylamide N,N-methylenebisacrylamide) and stirred in an ice bath for 1 hour. 0.02g initiator APS (ammonium persulfate) (equivalent to 1wt% of the monomer mass) was added and then stirred in an ice bath for 30s. The precursor solution was injected into the mold and sealed at room temperature for polymerization.
[0054] 1.1.3.3 Assembly of supercapacitor (SC) devices:
[0055] First, 80 mg AC, 10 mg conductive carbon black, and 10 mg PVDF were ground and an appropriate amount (1 ml) of NMP was added to form a uniform dispersion. The dispersion was then evenly applied to a carbon cloth and placed in a vacuum oven at 180 °C for 24 h to obtain an AC electrode. The mass of active material on each electrode was recorded. Two AC electrodes with the same mass of loaded active material were covered on the polyAM-DL 0.1 -LiCl3 hydrogel electrolyte on both sides to produce a “sandwich structure” of solid SC.
[0056] Example 2
[0057] Rapid polymerization mechanism
[0058] In the present invention, SD (synthesis details see attached Figure 6) can not only achieve strong interfacial adhesion, but also form a complex with the alkali metal ion LiCl through the coordination of catechol-metal, accelerate the establishment of the reversible reaction of quinone-catechol, activate the decomposition of the initiator APS, and produce sulfate radicals (SO4-·) and hydroxyl radicals (OH·), thereby initiating the rapid polymerization of AM monomers in the water-DES binary solvent. The synthesis of the low eutectic solvent is shown in the experimental section. The final hydrogel electrolyte is abbreviated as polyAM-SDx-LiCly-DESz, where x is the mass fraction of SD, y is the molar concentration of LiCl, and z is the volume percentage of DES.
[0059] LiCl and SD are the decisive factors for the rapid polymerization of AM monomers. Infrared thermal imaging showed that a large amount of heat was released after adding LiCl during the polymerization process ( Figure 2 a). The exotherm reached a peak at 80s, and then the temperature remained constant, indicating that the polymerization reaction was completed at 80s. In contrast, the AM precursor solution without LiCl under the same conditions ( Figure 8 ), no heat was generated after 600s. As the LiCl concentration increased from 0 to 5M, the gelation time was significantly shortened from 42min to 83s ( Figure 2 b). SD content also affects the gelation time. Figure 2 As shown in Figure c, with the increase of SD content, the gelation time first decreases and then increases. Although SD has a significant catalytic effect, excessive SD may eliminate free radicals and chain growth, thereby prolonging the polymerization time and even preventing the formation of gel ( Figure 2 c). In addition, further experimental data showed that the gelation rate of the hydrogel was negatively correlated with the content of DES ( Figure 2 d). After adding the low eutectic solvent, the proportion of water is reduced accordingly, and the generated OH· is reduced, resulting in a significant increase in the polymerization time. In addition, as the ambient temperature decreases, the gelation time will also increase ( Figure 2 e).
[0060] In order to further reveal the key mechanism of rapid polymerization of hydrogels and explore the effects of SD and LiCl on rapid polymerization, the present invention carried out X-ray photoelectron spectroscopy (XPS) analysis and electron spin resonance (ESR) spectroscopy tests. Figure 2 The XPS spectrum of f shows that when LiCl is not added, SD has a higher CO / C-OH peak at 286.4e V and a lower C=O peak at 288.9e V. When LiCl is added, the area of the CO / C-OH peak decreases, and the area of the C=O peak increases significantly ( Figure 2g). These data indicate that the -OH groups of SD were oxidized by APS to form semiquinone / quinone structures. In addition, UV-vis analysis of SD-LiCl solutions confirmed the formation of quinone and semiquinone groups, and the content of quinone / semiquinone groups gradually increased with increasing LiCl concentration ( Figure 2 h) From Figure 2 From the ESR spectrum of i, it can be seen that six peaks with similar relative intensities indicate the formation of SO4-·, and a quarter signal with a relative intensity of 1:2:2:1 confirms the presence of OH·. The catechol groups on SD are easily absorbed by the S2O8 2- Oxidized to quinone radical. At the same time, APS is reduced to SO4-·, which can interact with water molecules to produce OH·( Figure 2 j). These results indicate that the continuous generation of OH· during the polymerization process significantly increases the polymerization rate of the hydrogel without introducing additional energy.
[0061] Example 3
[0062] Adhesion properties of hydrogels
[0063] The adhesion strength of hydrogels is affected by two different factors: interfacial adhesion and cohesion. Interfacial adhesion refers to the strength of the bond between the hydrogel and the surface of the adhered object, and cohesion refers to the internal force that maintains the integrity of the hydrogel network. Adhesion failure of hydrogels can be attributed to interfacial adhesion failure or cohesive adhesion failure due to poor mechanical stability ( Figure 3 a). In the present work, SD containing a large number of catechol groups was introduced into the hydrogel to improve its interfacial adhesion and can firmly adhere to a variety of materials including metal, plastic, glass, wood, PTFE and rubber ( Fig. 9 To quantify the adhesion effect of the hydrogels, the adhesion strength of the hydrogels with different SD contents to the wood substrate was determined by lap shear strength test ( Fig.10 ). As the SD content increases, the adhesion strength gradually increases ( Figure 3 b) Preferred polyAM-SD 1.8 -LiCl5-DES 20 The hydrogels showed excellent interfacial adhesion to wood ( Figure 3 c). The excellent adhesion of the hydrogel is attributed to the synergistic effect of multiple interactions between the catechol groups and the substrate, such as hydrogen bonding, cation-π interactions, metal coordination, and hydrophobic interactions ( Figure 3 d).
[0064] The cohesion of the hydrogel determines the strength and durability of the hydrogel. During the lap shear test, when the cohesion is less than the interfacial adhesion, the hydrogel is limited by the cohesion failure, resulting in internal fracture and adhesion failure ( Figure 3e; Fig.11 ). The cohesion of the hydrogel can be controlled by adjusting the water content of the hydrogel. Figure 3 As shown in Figure 5, the water content of the hydrogel can be divided into three regions: when the water content is 20-23wt%, the adhesion strength drops sharply as the water content decreases; when the water content is less than 20wt%, there is almost no adhesion. When the water content is 23-50wt%, the adhesion strength increases significantly with the decrease of the water content. On the glass substrate, when the water content is 23wt%, the adhesion strength reaches a maximum value of 0.48MPa; when the water content exceeds 50wt%, the adhesion strength does not change much. The mechanical strength of the hydrogel also reflects the cohesive energy. When the water content decreases from 70wt% to 23wt%, the tensile strength increases from 0.06MPa to 2.28MPa ( Figure 3 g). At the same time, the modulus increased from 0.032MPa to 3.317MPa, an increase of about 103 times ( Fig.12 ). In addition, the thickness of the hydrogel is a factor that affects the adhesion strength. Figure 3 As shown in h, as the thickness increases, the adhesion strength decreases. The preferred water content of polyAM-SD is 23wt% 1.8 -LiCl5-DES 20 The hydrogel can adhere to different substrates such as glass (0.48MPa), wood (2.16MPa), metal (0.73MPa) and pig skin (0.097MPa). Figure 3 i). These adhesion values are among the highest reported for hydrogels (Table S1). Figure 3 A representative example of polyAM-SD bonded between two pieces of wood is shown in j. 1.8 -LiCl5-DES 20 The hydrogel can easily support a weight of 55kg.
[0065] Table S1. Comparison of various properties of hydrogels
[0066]
[0067] “---”: not available or not mentioned in the reference.
[0068] Example 4
[0069] Antifreeze and electrical conductivity of hydrogels
[0070] The hydrogel obtained by rapid polymerization in this embodiment not only has good adhesion but also has excellent antifreeze properties. Figure 4 As shown in a, after freezing at -60 °C for 3 h, the pure hydrogel became hard and brittle due to the formation of ice crystals in the gel network. 1.8-LiCl5-DES 20 The hydrogel maintained a certain degree of flexibility and could be stretched to 4 times its initial state at -60°C. The antifreeze property of the hydrogel is attributed to the destruction of hydrogen bonds between water molecules by DES. Raman spectroscopy ( Figure 4 b) shows that after adding 20wt% DES, polyAM-SD 1.8 -LiCl5-DES 20 At 3430cm -1 The peak at 3420 cm-1 was blue-shifted to 3420 cm-2. -1 , polyAM-SD 1.8 -LiCl5-DES 20 At 3430cm -1 The peak at 3380 cm-1 is further blue-shifted to 3380 cm-1. -1 , indicating that DES and LiCl can effectively destroy the hydrogen bonds between water molecules, thereby inhibiting the formation of ice at low temperatures. Differential scanning calorimetry (DSC) also revealed that when the DES content was 0, 20 and 40%, the freezing points of the hydrogels were -8.73, -42.72 and -50.21°C, respectively ( Figure 4 c). polyAM-SD 1.8 -LiCl5-DES 20 There is no freezing peak in the entire thermal analysis diagram, indicating that it has excellent antifreeze performance.
[0071] In addition to antifreeze properties, the hydrogel electrolyte of the present invention also exhibits excellent conductivity and adhesion at low temperatures. The conductivity of electrolytes with different LiCl concentrations measured at different temperatures is shown in Figure 2. Figure 4 d. The ionic conductivity of the electrolyte is linearly related to the inverse of the absolute temperature and follows the Arrhenius law. The activation energy (Ea) is the energy barrier that must be overcome for ion migration. The smaller the Ea, the easier the ion migration. At a low temperature of -40°C, as the LiCl concentration increases, Ea increases from polyAM-SD 1.8 -LiCl0-DES 20 26 kJ mol -1 Reduced to polyAM-SD 1.8 -LiCl5-DES 20 12.7 kJ mol -1 , the corresponding conductivity ranges from 0.1 mS cm -1 Increased to 1.58 mS cm -1 In order to illustrate the conductivity and adhesion of hydrogels at low temperatures, a simple experimental setup was designed, such as Figure 4 As shown in e, polyAM-SD 1.8 -LiCl5-DES 20The two steel plates glued together can light up the bulb when carrying a 1kg weight. Importantly, when the device is immersed in liquid nitrogen, the steel plates can still lift the weight and the bulb does not go out ( Figure 4 f). These results indicate that polyAM-SD 1.8 -LiCl5-DES 20 Not only does it achieve strong adhesion in liquid nitrogen, but it also has good low-temperature conductivity.
[0072] Example 5
[0073] Electrochemical performance of assembled supercapacitors (SCs)
[0074] The excellent adhesion and ion conductivity make the hydrogel of the present invention have good electrochemical performance in SCs. With carbon cloth and activated carbon as electrodes, polyAM-SD 1.8 -LiC5-DES 20 The hydrogel is a solid electrolyte, and the sandwich structure SC is assembled. The thickness of the electrolyte in the SC is about 0.3mm ( Fig.13 ). First, the electrochemical window and scanning speed of SC are determined by the control variable method. When the electrochemical window reaches 1V ( Fig.14 a), scanning speed is 50 m V s -1 hour( Fig.14 b), the cyclic voltammetry (CV) curve of SC shows a nearly perfect rectangle. The constant current charge-discharge (GCD) curves at different current densities also show a standard triangle and negligible voltage drop ( Fig.15 ). These data indicate that SC exhibits ideal double-layer capacitance behavior. When the temperature drops below zero, the CV curve of SC gradually changes from a rectangular shape at 25°C to a slightly deformed rectangular shape at -40°C ( Figure 5 a). The GCD curves at different temperatures are regular inverted triangles ( Figure 5 b). Electrochemical impedance spectroscopy (EIS) shows that the resistance of the SC increases from 10Ω at 25℃ to 60Ω at -40℃ ( Figure 5 c) The EIS curve shows the ability of ion migration. The EIS curve in the low-frequency region is almost perpendicular to the X-axis, indicating that polyAM-SD 1.8 -LiC5-DES 20 The electrolyte has good ion diffusion capacity.
[0075] In addition to the above antifreeze properties, polyAM-SD 1.8 -LiC5-DES 20 The strong adhesion of the hydrogel electrolyte to the electrode can avoid relative displacement or even delamination during repeated mechanical deformation ( Figure 5 d), which is beneficial to enhance the electrochemical stability of flexible supercapacitors in practical applications. Fig.16 and Figure 5 As shown in e, SC exhibits similar GCD curves at different bending states (0°, 45°, 90°, 180°). The specific capacitance calculated from these GCD curves shows that when SC is bent to 180°, the capacitance retention rate is 89.5% ( Figure 5 e) In order to further investigate the electrochemical stability of SC, the present invention conducted a cycle study on the assembled SC at a bending angle of 180°. Figure 5 As shown in Figure 5, the GCD test of SC was performed after every 500 bending / release cycles. The results show that the capacitance retention of SC decreased slightly after 500 bending cycles, and a high capacitance retention of 89.7% was still obtained after 2000 bending / release cycles ( Figure 5 g). The above data fully demonstrate that the SC assembled by the present invention has excellent durability and stability when facing high-intensity deformation. In addition, in order to achieve a higher voltage window and meet the requirements of practical applications, multiple SCs need to be connected in series. In the work of the present invention, when two devices are connected in series, the operating voltage can be extended to 2.0V ( Figure 5 h). More importantly, polyAM-SD 1.8 -LiC5-DES 20 The combination of strong adhesion and excellent antifreeze ability of the hydrogel electrolyte enables five SCs in series to light up an LED lamp at -40°C even after 2000 cycles of 180° bending. Figure 5 i). Therefore, the above results strongly prove the improvement of the key properties of the SC assembled by the present invention in terms of frost resistance, cycle life and deformation stability, indicating that polyAM-SD 1.8 -LiC5-DES 20 Hydrogel electrolytes are highly competitive in energy storage devices.
[0076] In summary, the present invention designed a self-catalytic system and successfully synthesized a conductive hydrogel with excellent adhesion and good antifreeze properties. The addition of a low eutectic solvent (DES) destroyed the hydrogen bonds between water molecules and enhanced the antifreeze property of the hydrogel. Dopamine-modified sodium alginate (SD) not only enhanced the adhesion, but also underwent a self-catalytic reaction with LiCl. By adjusting the concentrations of SD and LiCl, the polymerization process was completed within 83s. By simultaneously adjusting the interfacial adhesion and cohesion, a strong adhesion of 2.16MPa to wood was achieved. The resulting hydrogel electrolyte has a conductivity of 1.58mS cm at -40°C. -1The low-temperature conductivity of the electrolyte-assembled supercapacitor can resist the delamination / displacement of the multilayer structure during deformation, and the capacitance retention rate is 89.7% after 2000 bending / release cycles. In general, the present study demonstrates a general strategy for the rapid preparation of multifunctional hydrogel electrolytes for the development of stable and high-performance energy storage devices.
Claims
1. A catechol-alkali metal ion autocatalytic hydrogel electrolyte with high adhesion strength and antifreeze performance, characterized in that: The hydrogel electrolyte is prepared by the following method: Step 1: Synthesis of dopamine-modified sodium alginate SD SD was synthesized using standard carbodiimide coupling chemistry, EDC / NHS; Sodium alginate was dissolved in distilled water, stirred, and dissolved in a nitrogen atmosphere to prepare a 2.5wt% homogeneous sodium alginate solution; EDC and NHS were slowly added, reacted at room temperature for 3 hours, dopamine hydrochloride was added, the pH was adjusted to 7.8 with sodium hydroxide solution, and reacted at room temperature for 24 hours; finally, under the protection of nitrogen, unreacted reactants were removed by dialysis, and the product was freeze-dried; Step 2: polyAM-SD x -LiCl y -DES z Preparation of electrolyte: To prepare the deep eutectic solvent DES, choline chloride ChCl and ethylene glycol EG were mixed and stirred at 80°C until a transparent liquid was obtained to obtain DES; in the presence of SD and lithium chloride, polyAM-SDx-LiCly-DESz hydrogel electrolyte was obtained by polymerization of acrylamide AM; x is the mass fraction of SD, y is the molar concentration of LiCl, and z is the volume percentage of DES.
2. The hydrogel electrolyte according to claim 1, characterized in that The antifreeze and electrical conductivity of the hydrogel electrolyte are: at -40°C, 1.58 mS cm -1 , and strong adhesion 2.16MPa.
3. The hydrogel electrolyte according to claim 1, characterized in that In the step 1, 3.451 g of EDC and 2.072 g of NHS were added, and 0.6 g of dopamine hydrochloride was added to the solution.
4. The hydrogel electrolyte according to claim 1, characterized in that In the step 2, the molar ratio n(ChCl):n(EG)=1:
2.
5. The hydrogel electrolyte according to claim 1, characterized in that Step 2: First, lithium chloride was added to a mixture of DES and water with a DES volume fraction of 0, 20, 40, 60, and 80% to prepare a lithium chloride concentration of 0-7M, and then AM was added; then SD with a mass ratio of 0.3wt%, 0.6wt%, 1.2wt%, 1.2wt%, 1.8wt%, and 2.4wt% was added to the lithium chloride solution, and then MBA was added and stirred in an ice bath for 1 hour. Initiator APS was added, equivalent to 1% of the monomer mass, and then stirred in an ice bath; the precursor solution was injected into the mold and sealed at room temperature for polymerization.
6. A supercapacitor, characterized in that: Comprising any one of claims 1-polyAM-SD x -LiCl y -DES z Hydrogel electrolyte.
7. An assembly method using the supercapacitor according to claim 4, characterized in that: Here are the steps: First, activated carbon AC, conductive carbon black, and polyvinylidene fluoride PVDF were ground and N-methylpyrrolidone NMP was added to form a uniform dispersion; the dispersion was then uniformly applied on carbon cloth and placed in a vacuum oven at 180 °C for 24 h to obtain an AC electrode; the mass of active material on each electrode was recorded; two AC electrodes with the same mass of loaded active material were covered on polyAM-DL 0.1 -LiCl 3 The hydrogel electrolyte is placed on both sides to produce a "sandwich structure" of solid SC.